Detection of Toxoplasma Gondii in Cats and Seroprevalence in Women - Khayat, Fadia A. A. Al- (Indian Journal of Veterinary Sciences and Biotechnology, 2022)
This study aimed to investigate the potential threat of domestic and stray cats to public health in transmitting the toxoplasmosis. One hundred and sixty samples (40 blood samples from owner, 40 blood samples from non owner women, 40 fecal samples from their cats, and 40 fecal samples from stray cats) were analyzed. All blood samples were subjected to IgM, IgG rapid test for toxoplasmosis detection, while the fecal samples from cat were subjected to microscopic examination for the presence of the oocyst using direct wet mount as well as flotation method. The results revealed the total infection rate in women was 23.75% (19/80) with significant differences between cats owner (30.00%) and non- cats owner (17.50%). The IgG antibody was detected in 68.42% (13/19) amounting 8/19 (42.10%) in cats owner and 5/19 (26.31%) in non-cats owner, and the presence of both IgG and IgM antibodies was recorded in 6/19 (31.57%) of the infected women (21.05% and 10.52% for cats owner and non-cats owner, respectively). The total infection rate for cats was 16.25% (13/80), with highly significant differences p<0.001 between domestic cats (10.00%) and stray cats (22.50%).